Tracking the migration of cardially delivered therapeutic stem cells in vivo: state of the art. (May 2009) - Nyolczas, N; Charwat, S; Posa, A; Hemetsberger, R; Pavo, N; Hemetsberger, H; Pavo, IJ; Glogar, D; Maurer, G; Gyööngyöösi, M
Cell-based therapy is a promising, novel therapeutic strategy for cardiovascular disease. The rapid transition of this approach from the benchside to clinical trials has left a gap in the understanding of the mechanisms of cell therapy. Monitoring of cell homing and the fate of cardially delivered stem cells is fundamental for clarification of the myocardial regenerative process. Noninvasive imaging techniques allow an in vivo evaluation of the survival, migration and differentiation of implanted stem cells over time, and by this means, can help to answer unresolved questions. The most promising in vivo tracking methods involve the direct, nonspecific labeling of cells including MRI, radionuclide imaging and the use of reporter-gene imaging. This review summarizes the most important results of animal and human studies in which the fate and biodistribution of cardially delivered stem cells are assessed through different in vivo tracking methods.